Optimum flocculation conditions for the use of inorganic and polymer flocculants in powder form - Kadooka, Hiroto; Kiso, Yukari; Goto, S.; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2014)
Direct addition of dry composite flocculants in powder form to a colloidal suspension shows high reproducibil-ity of experimental data compared to the addition of a flocculant solution to the suspension. Utilizing this ad-vantage, the effects of inorganic and ionic polymer flocculants on turbidity removal have been investigated. Based on these observations, a procedure for determining the optimum composition of a composite dry powder flocculant for turbidity removal is proposed.